From Words to Sentences: Guiding Beginner ESL Students Through the Writing Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
For beginner learners of English as a Second Language (ESL), writing in English can be one of the most challenging skills to master. It requires an understanding of vocabulary, sentence structure, grammar, and the confidence to express ideas clearly. This article explores practical techniques for guiding these learners from recognizing individual words to constructing complete, meaningful sentences. It highlights step-by-step strategies that support vocabulary development, sentence structure awareness, and confidence-building in writing. In addition, the article discusses how modeling, shared writing, structured activities, and integrated language skills—such as speaking and reading—can foster a more comprehensive and supportive approach to writing instruction. Drawing on classroom-based methodologies and second language acquisition theories, the article offers educators accessible, research-informed methods for supporting the early stages of ESL writing development in a humanized and student-centered manner. These techniques aim to nurture student motivation, reduce writing anxiety, and encourage active participation in the learning process, laying a solid foundation for future academic and communicative success.